2020
DOI: 10.21203/rs.3.rs-106034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnic Differences in Spermatozoa Morphological Defects Diversity Among Men From Eastern Siberia, Russia

Abstract: Background.Sperm morphology defects are considered to indicate several spermiogenesis anomalies, resulting in decreased men fertility, causing not only poor sperm morphology but also increased DNA fragmentation, chromatin condensation defects, increased oxidative stress. Consequently, detailed assessment of sperm morphological abnormalities in additional to counting percentage of sperm with normal morphology may be useful for andrologists and reproductive biologists. However, a little attention is paid to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Previous study showed that men from the general population in Kemerovo had lowered sperm count, sperm concentration and progressive motility as well as serum testosterone and inhibin B level [56]. Regional variations of semen quality and sperm morphology are considered to be result of complex influences of various environmental conditions at the place of residence such as climate, trace elements in water or food, environmental pollution as well as lifestyle factors [51] and ethnic features associated with genetic background [60]. It should be noted that Novosibirsk and Kemerovo are located under the same climatic conditions and characterized by similar ethnicity of population and socio-cultural identity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that men from the general population in Kemerovo had lowered sperm count, sperm concentration and progressive motility as well as serum testosterone and inhibin B level [56]. Regional variations of semen quality and sperm morphology are considered to be result of complex influences of various environmental conditions at the place of residence such as climate, trace elements in water or food, environmental pollution as well as lifestyle factors [51] and ethnic features associated with genetic background [60]. It should be noted that Novosibirsk and Kemerovo are located under the same climatic conditions and characterized by similar ethnicity of population and socio-cultural identity.…”
Section: Discussionmentioning
confidence: 99%